Effect of Chitosan and Acrylic Acid Addition to Acrylic Resin on Porosity and Streptococcus mutans Growth in Denture Base - Ismiyati, Titik; Alhasyimi, Ananto Ali (European Journal of Dentistry, 2022)
Objective This work aimed to determine the effect of adding chitosan and acrylic acid to acrylic resin denture base on the porosity of the material and the growth of Streptococcus mutans.Materials and Methods This study is an experimental laboratory research. Samples were divided into the following three groups (n = 10): group 1 was the control group, group 2 was the acrylic resin mixture with 1% chitosan and acrylate acid, and group 3 was the acrylic resin mixture with 2% chitosan and acrylate acid. S. mutans growth was tested using the dilution method, and porosity was examined using an optical microscope. Data were calculated by one-way analysis of variance (p < 0.05) and correlation analysis.Results The acrylic resin added with 2% chitosan and acrylic acid showed pores with an almost spherical shape and the smallest size. Significant difference (p < 0.05) was observed among all the groups. A positive and extremely strong correlation was found between porosity and S. mutans growth.Conclusion Chitosan and acrylic acid at 1 and 2% concentrations can be added to acrylic resin to minimize the porosity of the denture base and reduce the growth of S. mutans. A less porous denture is associated with a low S. mutans growth rate.
Keywords: chitosan; acrylic resin; denture base; porosity; Streptococcus mutans